The Effect of Using Computer Learning Programs on The Mastery of Sundanese Vocabulary Early Children - Atiasih, Atiasih; Nurhayati, Susan; Hadianti, Asti Nur (CV. Goresan Pena, 2024)
This study was motivated by the problem of the lack of mastery of the Sundanese vocabulary of group B children at TK Kartika X-I. These problems require a medium that can motivate and develop the ability to master Sundanese vocabulary in early childhood. One alternative is through a computer learning program (software). The purpose of this study is to determine whether there is an influence or improvement after using a computer learning program for color vocabulary, numbers, and objects. This research uses a quasi-experimental method, the research subjects are children of group B1 (experimental) and children of group B2 (control) at Kartika X-1 Bandung Kindergarten in the 2013/2014 academic year. The data that will be obtained are the results of observation, interviews, documentation, and tests. Researchers conducted pretests and posttests on both groups which will be compared to increase the mastery of Sundanese vocabulary. The results showed an effect of the Sundanese language learning program on the mastery of Sundanese vocabulary in the experimental group. The experimental group got an average of 77.4% while the control group amounted to 61.40%.